Plurality in environmental supply chain mechanisms: Differential effects on triple bottom line outcomes. Issue 8 (7th August 2017) - Paulraj, Antony; Blome, Constantin
Abstract : Purpose: The environmental management of supply chains has become increasingly relevant in the recent era. Extant research proposes two main forms of mechanisms – collaboration and evaluation – for environmental supply chain management. Despite the wide use of these mechanisms and the empirical insight into the fact that they could be adopted simultaneously, it is unknown if, and, at which levels, environmental collaboration (EC) and environmental evaluation (EE) could be complementary or substitutionary in nature. Therefore, the purpose of this paper is to gain a clear understanding into the plural forms of these mechanisms. Design/methodology/approach: The transaction cost economics and relational exchange theory are used to ground the research hypotheses. The results are based on survey data collected from 145 US manufacturing firms. The authors employ polynomial regression as well as the response surface methodology to test the proposed hypotheses. Findings: The results suggest that EC and EE can have an intriguing effect depending on the outcome measure. Specifically, the authors find the effects in the economic and the environmental/social domains to be significantly different. Originality/value: While scholars acknowledge that collaboration and evaluation could act as complements, extant research does not propose and test models that specifically capture complementary and substitutionary nature of these mechanisms. Accordingly, the study makes the first attempt to empirically test for the effects of the simultaneous pursuit of EC and EE.